(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
The study investigated the economic impact of flood on plantain production in Southern Ijaw Local Government Area, Bayelsa State, Nigeria. The specific objectives were to describe the socioeconomic characteristics of the respondents, evaluate the impact of flooding on the income of the farmers, compare the cost and returns associated with plantain production during flooded and non-flooded period, identity factors contributing to flooding, and identify farmers coping strategies during flooding in the study area. Multi-stage random sampling technique was used to select 80 farmers for the study. Primary data collected using questionnaire were analysed using descriptive and inferential statistics. The result showed that the mean age of the farmers was 56 years, majority (79%) of the farmers had no formal education. The result also showed that farmers had an average farm size of 0.82 hectares. The average household size was 6 persons per household, and mean farming experience was 12 years. Logistic regression results of impact of flooding showed that profit was significant (p<0.05), farm size and age of the farmer were significant (P<0.05) probability level. The farmers have Net Farm Income (NFI) of N 74,617.13/ha, and N 231,575.32/ha for flooded and non-flooded year respectively. The study identified blockage of natural channels, topography of the area, poor drainages, blockage of curvet, closure of dam, prolong rainfall and over flowing rivers as factors contributing to flooding. In addition to that the study also identified farmers’ coping strategies in the event of flooding to include opening natural water canals, making canoes to access flooded areas, building wooden platform to keep properties, building wooden platform to live on, diversification to fishing, anticipate early planting next season, early and premature harvesting and exit to other crop ventures with smaller gestation period. The study recommends environmental improvement via unblocking of curvets, unblocking of natural drainages, destroying building on canals, and sand filling of very low lands. Palliatives and other relieve materials should be available to assist flood victims, extension agents should sensitize farmers on the gains of having an insurance policy. Finally, the research institutes and scientific communities should come up with plantain cultivars that will have shorter gestation period and improved flood resilient.